Is community tenure facilitating investment in the commons for inclusive and sustainable development? - Gnych, S.; Lawry, S.; McLain, R.; Monterroso, I.; Adhikary, A. (Elsevier, 2020)
With communities in many parts of the world achieving stronger, legally recognized, collective rights over their forests and other natural resources, important questions arise regarding how communities can overcome perceived barriers to investment and deliver sustainable development. Normative economic theory posits conceptual and practical barriers to investment in commons-based enterprises. This paper considers evidence and draws on lessons from four countries—Guatemala, Mexico, Nepal, where communities have been granted rights to forests, and Namibia, where communities have significant new rights to wildlife—to better understand the pathways emerging to deliver investment in the commons. We find that investment in community-owned resources is taking place and describe a process of "investment readiness." During a first stage, rights devolution triggers inward investment and development of community user groups and sustainable resource management plans subject to government review and approval. In a second stage, social enterprises, commonly referred to as Community Forest Enterprises (CFEs), are spawned or licensed by the community user groups. Stronger local social capital and the effective performance of local enterprises attract new forms of private investment in a third phase. Improved community capacity enables diversification and investment into new sectors, linking to value chains that adhere to global market and environmental standards. Progress from one stage to the next is in part conditional on increases in the level of assurance stakeholders have that the obligations of each party will be met. We also find that community rights have fostered investment that recognizes the social character of commons ownership, to deliver environmental and social returns, as well as profits. CFEs help drive social innovation in rural regions by solving social, economic and resource governance problems that neither the state nor the market has proved capable of addressing. CFE-based solutions remain experimental and fragile, however, and longer-term success of community-based forest enterprise depends on states and markets adopting innovations of their own that are supportive and not corrosive of community-based resource governance and development.